2011
DOI: 10.3357/asem.2908.2011
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Equivalence of Normobaric and Hypobaric Exposures of Humans to 25,000 Feet (7620 m)

Abstract: Alveolar gas composition and arterial hemoglobin oxygen desaturation patterns differed between a ground level and hypobaric exposure. Differences in mean number of hypoxia symptoms between hypobaric and normobaric environments after 1 min, but not at 3 and 4 min, coupled with similar patterns in symptom frequencies, suggest that ground-level hypoxia training may be a sufficiently faithful surrogate for altitude chamber training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 11 publications
3
49
0
Order By: Relevance
“…Of the studies, seven reported randomizing the exposure order ( 11,20,21,31,36,37,39 ), while three did not for logistical or unmentioned reasons ( 18,38,41 ). Washout periods between exposures ranged from multiple same day exposures ( 11,21,38 ) to 24 h ( 39 ) to 1 wk ( 18,20,31,36,37 ).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Of the studies, seven reported randomizing the exposure order ( 11,20,21,31,36,37,39 ), while three did not for logistical or unmentioned reasons ( 18,38,41 ). Washout periods between exposures ranged from multiple same day exposures ( 11,21,38 ) to 24 h ( 39 ) to 1 wk ( 18,20,31,36,37 ).…”
Section: Methodsmentioning
confidence: 98%
“…There were 10 major studies that compared HH to an NH equivalent with 4 considering hypobaria ( 18,20,21,31 ) and 2 others combining hypobaria with hypoxia ( 11,39 ). Of the 10, 3 of the studies ( 18,21,38 ) included women; no note was made regarding variations in ventilation due to changes in the menstrual cycle. The selected studies ( Table I ) had samples ranging from 6 to 43 participants with an overall mean of 15.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Protocol discrepancies (duration and level of altitude exposure) are common. There is a suggestion that the initial responses of oxygen saturation and symptoms of hypoxia are infl uenced by the protocol employed, but these differences were lost after 5 min [ 98 ]. Also, Savourey et al [ 99 ] observed initially higher respiratory frequencies and lower tidal volumes in hypobaric hypoxia than in the equivalent normobaric hypoxia, with lower end tidal oxygen and carbon dioxide levels, and lower oxygen saturations after 5 min of exposure.…”
Section: Differences Between Hypobaric and Normobaric Hypoxiamentioning
confidence: 99%